Comparison of clinical and morphological characteristics of Staphylococcus aureus endocarditis with endocarditis caused by other pathogens. Issue 7 (14th June 2005) - Nadji, G; Rémadi, J P; Coviaux, F; Ali Mirode, A; Brahim, A; Enriquez-Sarano, M; Tribouilloy, C
Abstract : Objectives: To analyse clinical, echocardiographic, and prognostic characteristics of Staphylococcus aureus infective endocarditis (IE) compared with endocarditis caused by other pathogens. Design: Cohort study. Methods: 194 consecutive patients with definite IE according to the Duke criteria prospectively examined by transthoracic and transoesophageal echocardiography were enrolled. Patients without identified microorganisms were excluded. The S aureus IE group (n = 61) was compared with the group with IE caused by other pathogens (n = 133). Results: Compared with IE caused by other pathogens, S aureus IE was characterised by severe co-morbidity, a shorter duration of symptoms before diagnosis, and a higher prevalence of right sided IE, cutaneous portal of entry, and history of renal failure. Severe sepsis, major neurological events, and multiple organ failure were more frequent during the acute phase in S aureus IE. In-hospital mortality (34% v 10%, p < 0.001) was higher in patients with S aureus IE and the 36 month actuarial survival rate was lower in S aureus IE than in IE caused by other pathogens (47% v 68%, p = 0.002). Multivariate analyses identified S aureus infection as a predictive factor for in-hospital mortality and for overall mortality. Conclusions: S aureus IE compared with IE caused by other pathogens occurs in a more debilitated clinical setting and is characterised by a higher prevalence of severe sepsis, major neurological events, and multiple organ failure leading to higher mortality.